And then 'Friends' - Kieran Tranter (Law, Technology and Humans, 2021)
This brief editorial focuses on the contribution in this volume titled ‘Machines Will Never Replace Humans!’ compiled by GPT-3. The brief text is provocative. It is provocative in demonstrating the potential efficiencies and complexities of machine-produced natural language text for ‘writing’ professions like law and the academy. It is further provocative as it reflects back the image and representation of the human within the digital. There is a denotive suggestion that humans are valuable and significant as lawyers because they possess intuition. There is a further suggestion that humans, or more precisely the imprint of humans in the digital, are televisual consumers of dated sitcoms, revealing the disconnect between existent digital archives and the totality of humanity.